Deconstruction. Critical Interventions for the 21st Century and Beyond - Gunkel, David J. (Studia Philosophiae Christianae, 2022)
This essay seeks to make a case for deconstruction as a kind of critical intervention for responding to and dealing with the opportunities and challenges of the 21st century and beyond. Toward this end, it proceeds in three steps or movements. (1) The first part will deconstruct deconstruction, deliberately employing what will be revealed as an inaccurate vernacular understanding of the term in order to extract a more precise and technical characterization of the concept. (2) The second part will investigate the constitutive elements of deconstruction, focusing attention on its two-step procedure, which has been deliberately designed to be a kind of distortion of Hegelian dialectics. (3) Finally, the third part will examine the opportunities and the challenges of the theory and practice of deconstruction indicating how and why it can be considered a critical intervention, albeit one that is not without its own potential problems and vulnerabilities. ------------------------- Received: 29/10/2022. Reviewed: 13/12/2022. Accepted: 23/12/2022.